(untitled) (Global Journal of Medical Research, 2020)
Chronic renal failure is a disease considered as a catastrophic disease; moreover, it is among the first 50 leading causes of death in Latin America. This disease presents several manifestations at the oral cavity with a big dental importance because they can affect the oral health of patients with chronic renal insufficiency. The objective of this study was to determine the frequency of oral, dental and periodontal manifestations in patients with chronic renal insufficiency treated with hemodialysis, who are attended at the "NEFROLOGY" center through a cross-sectional study of 62 patients who approved the inclusion criteria. A direct clinical observation of oral manifestations, periodontal examination, and epidemiological indices of oral morbidity (CPO, Oral Hygiene of Greene-Vermillion and O’Leary’s dentobacterial plate) were performed. The results were obtained using the x 2 test p